O efeito de cinco doses de cajuína em indivíduos destreinados submetidos a uma corrida até a exaustão - Oliveira, José Klinger da Silva de (2025)
Intense exercise increases the production of reactive oxygen (ROS) and nitrogen species (RNS), leading to oxidative stress, tissue damage, and alterations in cardiac autonomic function. Untrained individuals, with a lower capacity to cope with this stress, are more vulnerable to its adverse effects. Cajuína, a beverage rich in antioxidants such as polyphenols and vitamin C, in addition to its sociocultural value, may help mitigate the effects of intense exercise. This study investigated the effects of consuming five doses of cajuína on biomarkers, cardiac autonomic function, and physical performance in untrained individuals during a run to exhaustion. A randomized, double-blind, parallel-group, repeated-measures experimental study was conducted. Thirteen untrained men were randomized to consume five doses of either cajuína or a placebo, with the final dose ingested one hour before the running protocol at 80% of VO2 max. Blood samples were collected at four time points: baseline, pre-exercise, post-exercise, and 72 hours post-exercise. Malondialdehyde (MDA), creatine kinase (CK), lactate dehydrogenase (LDH), AST, ALT, and albumin were analyzed. Additionally, heart rate variability (HRV) parameters, as well as time and distance to exhaustion, were assessed. Results showed no differences between groups in time and distance to exhaustion (p≥0.05). Although CK and LDH levels did not differ significantly between groups (p≥0.05), the cajuína group showed a significant reduction in MDA levels post-exercise (p=0.001, d=0.64), with a significant group effect (p=0.001, d=1.59). For AST and ALT, the placebo group experienced significant post-exercise increases (p=0.001), with significant between-group differences in AST levels. Albumin levels were significantly higher in the placebo group pre-exercise and 72 hours post-exercise. Additionally, the root mean square of successive differences between RR intervals (rMSSD) and the standard deviation of RR intervals (SDNN) decreased substantially after exercise (p=0.001). In the placebo group, high-frequency (HF) power increased while lowfrequency (LF) power decreased, along with changes in the LF/HF ratio (p=0.001). In conclusion, consuming five doses of cajuína attenuated oxidative stress, reduced tissue damage, and supported cardiac autonomic function in untrained individuals following intense exercise, suggesting its potential as an antioxidant strategy in high-effort physical contexts.